Drabina hierarchiczności wśród więźniów deportowanych z Francji. Case study Drancy, przedsionka Auschwitz - Chrząszcz, Paulina (Instytut Historii PAN, 2025)
The purpose of this article is to analyse the phenomenon and process of hierar-chisation of prisoners of the Drancy concentration camp, a pre-deportation threshold to Auschwitz-Birkenau. The analysis concerns French deportees, mainly of Jewish origin. Initially, the article was intended to address the problem of the hierarchy among Auschwitz prisoners; however, during the research, it was decided that due to the large amount of material, it would be better to divide the text into two separate articles, treating these internment centres separately. The text is the result of months of research and investigation conducted primarily abroad, aimed at understanding the phenomenon of prisoner hierarchy. The sources used in this article mainly include resources from the Mémorial de la Shoah in Paris (and its Drancy branch) as well as documents from the Polish Institute of National Remembrance, film sources (including documentaries and oral history interviews addressing the issues of hierarchy among prisoners).
p. 147-171
Summary in English.
Keywords: Drancy; concentration camps; prison structures; prison hierarchy; French Jews; Holocaust, Jewish (1939-1945) - France; Drancy (France; concentration camp); World War (1939-1945) - concentration camps - France